The “two-step” yielding process of the natural mud under steady and oscillatory shear stress - Wang, Shaohua; He, Zhiguo; Gu, Hengye; Xia, Yuezhang (Frontiers in Earth Science, 2022)
The rheological properties of natural mud are closely related to nautical depth estimation, wave propagation, and morphology evolution of muddy coast. In this study, the rheological properties of the natural mud collected from Luxi Island and Zhoushan Island in China were investigated. Shear stresses in steady state or oscillatory state were imposed on mud samples directly to obtain the yielding process under tidal currents or waves. The results showed that both apparent viscosity and complex viscosity experienced two sharp declines with increasing shear stress, indicating a two-step yielding nature of natural mud. Two yield stresses, namely static yield stress and fluidic yield stress correspond to the yielding processes of elasticity and viscosity breakdown, respectively. The static yield stress in the oscillatory shear stress tests was lower than in steady shear stress tests, and the fluidic yield stress of natural mud in oscillatory shear stress tests was higher than in steady shear stress tests. The above phenomenon was explained by a viscoelastic-oscillation theory. Furthermore, experimental results indicated that the initial storage modulus had a closer connection to both yield stresses in comparison with mud density.